Narratives of women media practitioners in Cebu - Reyes, Fe N. (Iloilo City UP Visayas, 2007)
"The oral and written narratives of ten women media practitioners in Cebu show how they have become pioneers and pacesetters in a male-dominated industry. Interviews conducted with nine women media practitioners and an examination of the autobiographical writings of one deceased media pioneer reveal the evolution of women media practitioners in Cebu. The narrative of Briones represents the prewar period: Vamenta, the postwar period; Daluz, Cabaero, Paredes, Gonzales and Mangubat, the Martial Law period; and Sy, So and Amante, the postEDSA period. The women during the prewar and postwar periods were limited to writing on soft issues, were not considered authoritative to do newscast, and were subject to male derision. However, their socialization and exposure to strong role models in media enabled the women to transcend the limitations by being competent media practitioners. In the 1980s, formal training and professionalism in media emerged, and the women rose to editorial and decision-making positions. Their being vocal and exemplary in the setting of standards, their involvement in the training of reporters, their writing of award-winning reports, and their introduction to innovations are among their contributions to mass media. Despite questions regarding their capacity to be managers and the costs involved in pace setting work, the women set the pace through competence, courage and the support of family."
Keywords: Mass media -- Cebu City; Media practitioners